2020
DOI: 10.13189/ujer.2020.082574
|View full text |Cite
|
Sign up to set email alerts
|

Technologically Assisted Teaching Approach: The Visual-Only Video Teaching Strategy in the Nursing Education Classroom

Abstract: Due to the development of the technological devices and technologically assisted teaching and learning materials, tools, and strategies, the teaching and learning behaviors of both teachers and students have been changed. Currently, technology and visual learning tools are some of the effective tools for many classroom environments. The researcher's aim was to determine, understand and evaluate the effectiveness of the Visual-Only Video Teaching Strategy with nursing students and how this, together with a visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The CLT encourages teachers to employ related teaching and learning materials and tools from living communities and societies (Dos Santos, 2019) [3]. What's worse, affected by the testoriented teaching conditions in China, teachers seldom organize activities that provide students with enough time to speak.…”
Section: Lack Of Real Communication In the Classroommentioning
confidence: 99%
“…The CLT encourages teachers to employ related teaching and learning materials and tools from living communities and societies (Dos Santos, 2019) [3]. What's worse, affected by the testoriented teaching conditions in China, teachers seldom organize activities that provide students with enough time to speak.…”
Section: Lack Of Real Communication In the Classroommentioning
confidence: 99%
“…Some recent studies indicated that flexibility, location-free access, and self-paced learning are key in distance-learning options and programmes. Although most students started their programmes with a face-to-face approach, many young adults are used to technologically-assisted teaching and learning options (Almog et al, 2018;Booy et al, 2012;Dos Santos, 2020a, 2021b, 2020c. Finding little difficulty in technology and online learning, many continued with their programmes.…”
Section: The Desire To Complete and Finish Education And Programmesmentioning
confidence: 99%